2021
DOI: 10.1186/s12958-021-00709-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel variants in DNAH9 lead to nonsyndromic severe asthenozoospermia

Abstract: Background Asthenozoospermia is one of the most common causes of male infertility, and its genetic etiology is poorly understood. DNAH9 is a core component of outer dynein arms in cilia and flagellum. It was reported that variants of DNAH9 (OMIM: 603330) might cause primary ciliary dyskinesia (PCD). However, variants in DNAH9 lead to nonsyndromic severe asthenozoospermia have yet to be reported. Methods Whole exome sequencing (WES) was performed fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Furthermore, mutations in DNAH1 , DNAH2 , DNAH8 , and DNAH17 have been shown to cause predominant male infertility, although mild PCD symptoms may be present [ 13 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Interestingly, asthenospermia without PCD symptoms was recently reported in two patients with DNAH9 mutations [ 50 ]. DNAH9 is a known PCD gene, which is required for distal ODA assembly in motile cilia and causes mild PCD symptoms [ 51 , 52 ].…”
Section: Role Of Pcd Genes In Male Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, mutations in DNAH1 , DNAH2 , DNAH8 , and DNAH17 have been shown to cause predominant male infertility, although mild PCD symptoms may be present [ 13 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Interestingly, asthenospermia without PCD symptoms was recently reported in two patients with DNAH9 mutations [ 50 ]. DNAH9 is a known PCD gene, which is required for distal ODA assembly in motile cilia and causes mild PCD symptoms [ 51 , 52 ].…”
Section: Role Of Pcd Genes In Male Fertilitymentioning
confidence: 99%
“…Similar estimates were reported for MMAF patients: 63–68%, 54–57%, and 43% for fertilization, pregnancy, and live birth rates, respectively [ 66 , 96 ]. Successful clinical pregnancies by various methods have been reported for couples with male partner PCD [ 57 , 61 , 62 , 83 , 84 , 85 , 86 , 97 , 98 , 99 , 100 , 101 ] and for some known PCD genes [ 50 , 66 , 102 , 103 , 104 ], as summarized in Table 3 .…”
Section: Success Of Art In Pcd Patientsmentioning
confidence: 99%
“…For instance, the DANH1 gene is a candidate gene for PCD, which encodes a core component of inner-arm heavy chain dynein, and an investigation carried out by Sha et al [ 24 ] demonstrated that 12 patients harboring DNAH1 variants only presented the MMAF phenotype in the absence of PCD-related symptoms. DNAH9 is another candidate gene for PCD, but Tang et al [ 25 ] reported that DNAH9 variants can result in non-syndromic severe asthenospermia without PCD-related symptoms. Based on this, MMAF may be another form of classical PCD [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…and DNAH17 (Asai & Wilkes, 2004). To date, biallelic variants in ten of these, DNAH1 (Wang et al, 2017), DNAH2 (Hwang et al, 2021), DNAH5-11 (He et al, 2020;Li et al, 2022;Liu et al, 2020;Oud et al, 2021;Tang et al, 2021;Wei et al, 2021;Zhu et al, 2019), and DNAH17 (Zhang et al, 2020) have been reported to be associated with human male infertility and asthenozoospermia.…”
Section: Discussionmentioning
confidence: 99%